An introduction to Campion Ohasio - David Robie (Asia Pacific Network, 2019)
Twenty five years ago in Melbourne I encountered a young cartoonist with a flair and panache that was remarkable. His name is Michael Leunig. At the time I was editor of the Sunday Observer and I felt Michael was destined for an astounding future. His distinctive whimsical and poetic style—Barry Humphries once described it as 'murky, melancholy and marvellous'—eventually took him to the top of Australian cartooning. His socially aware messages and his characteristic flippant duck were a remarkable antidote to the humourless puritans of the era. He once drew me a galivanting duck balancing a teapot on its head as I left Melbourne for greener pastures.